2022
DOI: 10.1155/2022/5456616
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Surgical Site Infection after Femoral Neck Fracture Surgery: An Observational Cohort Study of 2218 Patients

Abstract: Background. Surgical site infection (SSI) was a formidable challenge for surgical management of femoral neck fractures; however, there was a lack of studies with comprehensive variables. We conducted this study to investigate the incidence and risk factors of SSI in elderly patients with femoral neck fractures. Methods. This was a retrospective study of patients who presented with femoral neck fractures and underwent surgery in our institution between January 2016 and April 2020. All data were collected from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…As shown in Figure 2, all studies 8–10,19–27 were of high quality. However, limitations in two studies 8,24 and findings and conflicts of interest were not reported in two studies 8,20 …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…As shown in Figure 2, all studies 8–10,19–27 were of high quality. However, limitations in two studies 8,24 and findings and conflicts of interest were not reported in two studies 8,20 …”
Section: Resultsmentioning
confidence: 94%
“…Twenty‐three studies were removed owing to improper research design or outcomes, and 22 studies were discarded due to a lack of necessary data after carefully examining the full text of 55 studies. Finally, this systematic review and meta‐analysis included 12 studies 8–10,19–27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of SSI following malignant bone tumor surgery has been reported to be 3–10 times higher than that following general orthopedic surgery [ 6 , 7 ]. The incidence of SSI in patients who underwent orthopedic surgeries was reported as 0.2–4.2% [ 8 , 9 , 10 , 11 , 12 , 13 ]. The incidence of SSI in total hip arthroplasty was reported as 0.2% [ 13 ], whereas the incidences of SSI in spine surgeries were reported as 3.4–4.2% [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%